ILLUSTRATIVE MATERIALS IN CONTEMPORARY WORKBOOKS FOR LEARNING RUSSIAN IN SERBIAN SPEAKING ENVIRONMENT - Наташа Д. Ајџановић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2010)
In this paper the author tries to stress the importance of illustrations in workbooks aimed at learning foreign languages in general and Russian in particular. In order to do so, the author analyses two sets of workbooks used for learning Russian in Serbian primary schools.